Fatigue fracture behaviour of spot welded B1500HS steel under tensile‐shear load. Issue 8 (1st February 2015) - Wang, B.; Duan, Q. Q.; Yao, G.; Pang, J. C.; Zhang, Z. F.; Wang, L.; Li, X. W.
ABSTRACT The microstructural characterizations, micro‐hardness measurements and fatigue tests of B1500HS steel spot welded tensile‐shear specimens were performed. The high hardness values of base material (470 HV) and nugget (515 HV) are closely related to the dominant formation of martensitic microstructures, while the occurrence of soft zone is the result of the formation of ferrite phases in inter‐critical heat‐affected zone (HAZ), as well as martensite tempering in sub‐critical HAZ. The fatigue failure modes involve the fracture along the circumference or along the direction of width. The fatigue property of spot welded B1500HS is found to be better than that of spot welded M190 because of the thicker sheet and suitable nugget size, which follows the standard rule of 5t0.5, where t is the sheet thickness.